The Efficacy and Safety of Oral Ferrous Gluconate in Premenopausal Women with Severe Iron Deficiency Anaemia - Tazeen Fatima Munim; Shaista Rashid (KARACHI MEDICAL AND DENTAL COLLEGE, 2017)
Objective: To evaluate the efficacy and safety of ferrous gluconate, given orally thrice daily for three months, to pre-menopausal women with severe iron deficiency anaemia. Method:   A phase IV non randomized single arm open label drug trial was conducted at Gynaecology and Obstetrics Unit II in Abbasi Shaheed Hospital from Feb 2013 to March 2014, which is a 950 bedded public sector tertiary care hospital. Total fifty premenopausal women with documented severe iron deficiency anaemia, haemoglobin (Hb) between 6-8 g/dl were enrolled after taking written informed consent. Clinical evaluation and lab in- vestigation for serum ferritin and haemoglobin  levels  were  conducted  at  baseline  and  after  comple-  tion of treatment. A standardized proforma for data collection was developed. Ferrous  gluconate  soft gelatin capsules were given as one capsule during or after the meal 3 times daily, for three months. All patients were evaluated four times during study first at the time of enrolment and after 30, 60, and 90 days for clinical efficacy and safety assessment. Results: In our study all fifty premenopausal women completed iron treatment. Analysis of therapeutic efficacy parameters i.e. haemoglobin, and serum ferritin levels showed improvement that was sta- tistically significant. By the end of treatment with oral ferrous gluconate, significant improvement in Hb   levels was observed (7.574 ± 0.559  g/dl  vs  11.020  ±  0.718,  p<0.0001).  Significant  changes  were  noted in serum ferritin level (10.058 ± 5.059 ng/ml vs 27.136 ±  13.803,  p<0.0001)  after  3  months  therapy. Ferrous gluconate proved to be safe in women  with  severe  iron  deficiency  anaemia.  The  treated women did not exhibit any major side effect,  only  one  serious  side  effect  was  reported  (erythema nodosum). Mild self-limiting side  effects  including  black  discolouration  of  stool  in  54%  cases, nausea in 6%, constipation in 2% and diarrhoea in 2% was observed. Conclusion: Oral ferrous gluconate treatment for severe iron deficiency anaemia is well tolerated and highly effective in premenopausal women.